Adolescents Plan to be Reproductive Healthy and Risk-Free of HIV Infection through Health Education based on Agricultural Perspective: Remaja Berencana Sehat Reproduksi dan Bebas Risiko Tertular HIV melalui Penyuluhan Berwawasan Agrikultura - Dicky Endrian Kurniawan; Afandi Alfid Tri; Purwandari Retno; Ardiana Anisah; Khamid M. Nur; Kholid Rosyidi Muhammad Nur; Enggal Hadi Kurniyawan (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
HIV incidence attacks not only the adult population but also cases that occur in adolescents. The incidence of HIV in adolescents is related to the behavior of adolescents in maintaining their reproductive health. Therefore, efforts must be made to increase youth awareness of reproductive health and prevent HIV transmission. Health education, outreach, and discussions will be held on Thursday, 30 March 2023, at a high school in Jember at 08.00 WIB - finished. The target audience for this activity was students from a high school. Service activities by providing health education so that youth can take an active role and participate in solving HIV AIDS prevention problems. Health education is an effort to increase the knowledge and awareness of individuals by providing information with counseling and discussion methods. This activity showed that most youths demonstrated that they could understand how to maintain reproductive health and HIV AIDS prevention from an agricultural perspective. As feedback, adolescents stated that they were willing to support reproductive health and prevent the transmission of HIV AIDS. As a suggestion, it is hoped that youth can increase their role and participate actively in maintaining adolescent reproductive health and tackling HIV AIDS. In addition, the community is expected to actively implement government recommendations in maintaining health, especially in preserving reproductive health and preventing the transmission of HIV AIDS.